Editorial board, information for authors, and other front matter - Ricky Telg (Journal of Applied Communications, 2012)
This content includes the front cover, the table of contents, editorial and other information for authors for vol. 96, no. 1(2012) of Journal of Applied Communications
Keywords: masthead